Acute hepatitis A virus infection in patients hospitalized at the Department of Infectious Diseases, Medical University of Lublin (Eastern Poland) in 2017 – a hospital-based retrospective study - Krzowska-Firych, Joanna Małgorzata; Ściślak, Robert; Wójtowicz, Agnieszka; Tomasiewicz, Krzysztof; Lucas, Georgia; Lucas, Christiana (Clinical and Experimental Hepatology, 2018)
The aim of our study was to analyze medical records of all adult patients with acute hepatitis A virus (HAV) infection who were hospitalized at the Department of Infectious Diseases, Medical University of Lublin, Poland in 2017. During the studied period acute HAV infection was confirmed in 33 patients. In the study group there were 30 men and 3 women. The mean time of hospitalization was 12 days. All patients recovered with no clinical sequelae.